2009
DOI: 10.1016/j.neulet.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

NMDAR blockade-induced neonatal brain injury: Reversal by the calcium channel agonist BayK 8644

Abstract: We have previously shown that P7 rat pups injected with the N-methyl-D-aspartate receptor (NMDAR) blockerMK801 displayed robust apoptotic injury within hours after injection. Further studies from our lab suggest that loss of calcium cannot be compensated for when vulnerable neurons lack calcium buffering capabilities. Thus, to elevate calcium in these neurons prior to MK801 exposure, we injected P7 rats with the calcium channel agonist BayK 8644. Whereas BayK 8644 did not induce apoptosis by itself, it was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…The time of the first injection was defined as time = 0 (t 0 ). For comparison with this and previous studies, we also injected MK801 at 1 mg/kg (one injection only at t 0 ), as this dose produces robust AC3 induction that is reliable and widespread (Turner et al, 2002, Turner et al, 2007b, Turner et al, 2009a). Sterile PBS (1 injection at 0, 1, 2 and 3 hours; 4 total) served as vehicle controls.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The time of the first injection was defined as time = 0 (t 0 ). For comparison with this and previous studies, we also injected MK801 at 1 mg/kg (one injection only at t 0 ), as this dose produces robust AC3 induction that is reliable and widespread (Turner et al, 2002, Turner et al, 2007b, Turner et al, 2009a). Sterile PBS (1 injection at 0, 1, 2 and 3 hours; 4 total) served as vehicle controls.…”
Section: Resultsmentioning
confidence: 95%
“…We referred to this sampling territory as the SSC ANT . Numbers of AC3-positive neurons were estimated within lamina IV and V of the SSC, as previous studies have reported reliable and robust injury in these layers (Turner et al, 2007b, Turner et al, 2009a, Turner et al, 2009b). For comparison, we also qualitatively evaluated AC3-positive profiles in the superficial portion of layer II/III in the same sections we sampled layers IV and V.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although morphology can guide us in the SSC ANT , where dying cells are typically pyramidal in shape [20,26], in other brain regions (Cg, CP) the phenotype is more varied [1,2,7,20]. Regardless, our data here and elsewhere suggest that a closer examination of the relationship between the GABA terminals and these dying cells might tell us more about why these cells are so vulnerable.…”
Section: For Higher Power Viewsmentioning
confidence: 62%